Examining the factors influencing information poverty in western China. Issue 5 (25th November 2020) - Mou, Xiaobo; Xu, Fang
Abstract : Purpose: The purpose of this study is to explore the factors impacting information poverty in western China and investigate to what extent these determinants contribute to information poverty in these areas. Design/methodology/approach: Structural equation modeling (SEM) technique was used to analyze 232 valid responses collected from a survey to examine the research model and hypotheses in this study. Findings: The results indicate that information literacy, information supply and information and communication technologies (ICTs) positively and significantly affect information poverty, while social prejudice and information orientation had no significant effects on information poverty. Practical implications: Public libraries, government departments and other institutions should pay attention to the significant impact of information literacy, information supply and ICTs on information poverty and formulate corresponding systems and policies to alleviate or reduce information poverty. Originality/values: In the past, few studies have focused on information poverty in western China and most of the existing research on information poverty adopts qualitative research methods, such as interview, systematic literature review and so on, while quantitative research is rare. In addition, the focus of these research studies was on one or two aspects, and a few of them can systematically study the influencing factors of information poverty. Inspired by the theories of information literacy, social prejudice and information poverty, this study comprehensively used a questionnaire survey and SEM to investigate the influences of information literacy, social prejudice, information supply, information orientation and ICTs on information poverty.